Frequency and species richness of termites in eucalyptus plantations in the north coast of Bahia, Brazil - Sales, Maria José Dias; Matos, William Costa; Reis, Yana Teixeira dos; Ribeiro, Genésio Tâmara (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the frequency and species richness of termites which occur in eucalyptus reforestation areas. The samples were collected from three recently harvested Eucalyptus areas, in December 2005, in 100 m-long and 2 m-wide transects, divided into 20 contiguous plots (2x5 m). Each plot was sampled for one hour per person, and from each subdivision, 12 disturbed soil samples were taken from 20x20x20 cm, from which 21 species of termites belonging to two families and 16 genera were collected. Ten species were found to be dominant, all belonging to the family Termitidae, from which those with the highest frequency were Amitermes amifer and Nasutitermes corniger. The functional group xylophages had the highest number of species (11) and the highest frequency. Species known as pests in eucalyptus had a frequency below the limit of dominance.